Ultrasound Guided Needle Aspiration of Breast Abscess as an Alternative to Surgical Incision and Drainage (TAJ: Journal of Teachers Association, 2020)
Breast abscess is the localized collection of pus in breast tissue. Various treatment protocols used now a day like oral drugs, hot compression, surgical incision and drainage and ultrasound guided needle aspiration. Aim of this article was to identify the ultrasound guided needle aspiration of breast abscess is an alternative to surgical incision and drainage by analysis of previous study reports. It was found that though ultrasound guided aspiration of breast abscess has some benefit than traditional surgical drainage but it not applicable for all cases.TAJ 2020; 33(1): 1-4